2013
DOI: 10.1111/jsap.12154
|View full text |Cite
|
Sign up to set email alerts
|

Carbimazole‐associated hypersensitivity vasculitis in a cat

Abstract: Feline hyperthyroidism can be treated medically, surgically or with radioactive iodine. Carbimazole inhibits both triiodothyronine and thyroxine synthesis in the thyroid gland and reported side effects include mild eosinophilia, leucopenia and lymphocytosis, thrombocytopenia, elevated liver enzyme activities, gastrointestinal signs and skin abnormalities. This case report describes a cat with carbimazole-associated apparent hypersensitivity vasculitis causing digital and tail necrosis, with multiple renal infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…7 Use of a limited-iodine diet avoids the frequently observed side effects of antithyroid medications. [8][9][10] A recent study found that cats previously treated with antithyroid drugs had improved feline hyperthyroidism clinical signs and a significant reduction in serum thyroid hormones when fed a limited-iodine food, indicating that nutritional management is a viable alternative and is not influenced by prior antithyroid drug treatment. 4 Various investigators have demonstrated that a limited-iodine food, generally defined as <0.3 ppm on a dry-matter basis (DMB), 4,11 is effective in decreasing concentrations of circulating thyroid hormones by reducing intake of iodine trace amounts needed for thyroid hormone synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Use of a limited-iodine diet avoids the frequently observed side effects of antithyroid medications. [8][9][10] A recent study found that cats previously treated with antithyroid drugs had improved feline hyperthyroidism clinical signs and a significant reduction in serum thyroid hormones when fed a limited-iodine food, indicating that nutritional management is a viable alternative and is not influenced by prior antithyroid drug treatment. 4 Various investigators have demonstrated that a limited-iodine food, generally defined as <0.3 ppm on a dry-matter basis (DMB), 4,11 is effective in decreasing concentrations of circulating thyroid hormones by reducing intake of iodine trace amounts needed for thyroid hormone synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…7 Use of a limited-iodine diet avoids the frequently observed side effects of antithyroid medications. 810 A recent study found that cats previously treated with antithyroid drugs had improved feline hyperthyroidism clinical signs and a significant reduction in serum thyroid hormones when fed a limited-iodine food, indicating that nutritional management is a viable alternative and is not influenced by prior antithyroid drug treatment. 4…”
Section: Introductionmentioning
confidence: 99%